A process for producing moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology

By combining hydrophilic modification, false twist deformation, thermal setting, nanocoating and laser microstructure treatment, the problem of taking into account both the moisture absorption and fast drying and elasticity of polyester fibers in the prior art is solved, and the moisture absorption and fast drying and elasticity of polyester fibers are effectively improved, and the overall performance of the fabric is improved.

CN119777157APending Publication Date: 2025-04-08CHANGSHU YOUFU TEXTILE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937958.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the moisture absorption and rapid drying and elasticity of polyester fibers in the same technical solution, resulting in insufficient overall performance of the fabric.

Method used

The process based on false twist deformation technology is adopted, and the moisture absorption and rapid drying and elasticity of polyester fibers are improved by combining hydrophilic modification treatment, false twist deformation treatment, heat setting, nanocoating treatment and laser microstructure treatment.

Benefits of technology

It significantly improves the moisture absorption and quick drying properties of polyester fibers, while enhancing its elasticity and flexibility, improving the overall performance of the fabric, and is suitable for functional clothing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777157A_ABST
    Figure CN119777157A_ABST
Patent Text Reader

Abstract

The invention relates to the field of textile materials and processing technology thereof, and discloses a process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology, comprising the following steps: Step 1, raw material selection: selecting low-crystallinity, high-molecular-weight polyester fiber, wherein the molecular weight of the polyester fiber is 25,000 to 40,000, and the crystallinity is 40% to 60%; Step 2, hydrophilic modification treatment: soaking the polyester fiber in a hydrophilic chemical additive solution, wherein the hydrophilic chemical additive is polyvinyl alcohol or polyurethane, and the concentration of the additive solution is 0.1% to 1%, and the soaking time is 30 to 60 minutes, followed by water washing and drying. By combining the hydrophilic modification treatment with the laser microstructure treatment, the hygroscopicity and quick-drying properties of the polyester fiber are significantly improved, and the use of the hydrophilic chemical additive enhances the surface hydrophilicity of the polyester fiber, thereby increasing the water absorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile materials and processing thereof, in particular to a process for a moisture-absorbing, quick-drying, high-elastic polyester fabric based on a false-twist texturing technology. Background Art

[0002] As an important synthetic fiber material, polyester fiber is widely used in the textile industry due to its high strength, good wear resistance and excellent dimensional stability. However, due to the limitations of surface chemical properties, traditional polyester fiber has poor hygroscopicity and air permeability, and has certain deficiencies in moisture absorption, quick-drying performance and wearing comfort. In recent years, with the increasing demand for functional clothing, how to further improve the moisture absorption, quick-drying and wearing comfort of polyester fabrics has become a research focus.

[0003] In the prior art, the performance of polyester fabrics is usually improved by chemical modification and physical deformation. For example, hydrophilic chemical additives are often used to improve the hygroscopicity of polyester fibers, false twist texturing improves the elasticity and softness of polyester fibers by changing the fiber morphology, and laser microstructure treatment improves the air permeability and quick-drying performance of fabrics by forming a microporous structure on the fiber surface. However, the prior art is often independent of each other and fails to form an efficient and coordinated treatment solution.

[0004] The main problem with the existing technology is that although a single hydrophilic modification or physical deformation method can improve the hygroscopicity, elasticity or quick-drying performance of polyester fibers to a certain extent, it is impossible to achieve a comprehensive improvement in multiple performances in the same technical solution, especially it is difficult to strike a balance between hygroscopicity and quick drying and elasticity enhancement, resulting in insufficient overall fabric performance and limiting the further development and application of functional fabrics. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a process for producing moisture-absorbing, quick-drying and highly elastic polyester fabric based on false twist texturing technology, which solves the problem that the prior art cannot achieve comprehensive improvement of multiple performances in the same technical solution, especially the difficulty in balancing moisture absorption and quick drying with enhanced elasticity, resulting in insufficient overall performance of the fabric.

[0006] To achieve the above purpose, the present invention is implemented by the following technical scheme: a process for making moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology, comprising the following steps:

[0007] Step 1, raw material selection: select low crystallinity, high molecular weight polyester fiber, the molecular weight of the polyester fiber is 25000 to 40000, and the crystallinity is 40% to 60%;

[0008] Step 2: hydrophilic modification treatment: immerse the polyester fiber in a hydrophilic chemical additive solution, wherein the hydrophilic chemical additive is polyvinyl alcohol or polyurethane, the concentration of the additive solution is 0.1% to 1%, the immersion time is 30 to 60 minutes, and then wash and dry;

[0009] Step 3, false twist texturing: the polyester fiber after the hydrophilic modification is subjected to a false twist texturing device for texturing, with a twist range of 150 to 300 twists / m and a stretching ratio of 1.2 to 1.5 times;

[0010] Step 4, heat setting: placing the polyester fiber after false twisting and texturing in a heat setting device, the temperature range is 160°C to 200°C, the pressure range is 0.5 to 1.2 MPa, and the setting time is 3 to 5 minutes;

[0011] Step 5, nano coating treatment: coating the surface of the polyester fiber with a nano coating material by a sol-gel method, wherein the nano coating material is nano silicon dioxide or nano titanium dioxide, and the coating thickness ranges from 100 to 300 nm;

[0012] Step 6: Laser microstructure processing: Use laser etching technology to process the microstructure of the polyester fiber surface, the laser power is 20 to 50W, and the exposure time is 2 to 5 seconds.

[0013] Preferably, the molecular weight of the polyester fiber is 30,000 to 35,000, and the crystallinity is 45% to 55%.

[0014] Preferably, the concentration of the hydrophilic chemical additive solution is 0.5% to 1%, and the soaking temperature is 40°C to 60°C.

[0015] Preferably, the soaked polyester fiber undergoes a stepwise drying process at a temperature ranging from 80° C. to 120° C., the duration of which is 30 to 50 minutes.

[0016] Preferably, the false twist texturing process includes a primary twist process and a final twist process, the primary twist ranges from 150 to 200 twists / m, and the final twist ranges from 200 to 300 twists / m.

[0017] Preferably, in the heat setting step, the setting temperature is 180° C., the setting pressure is 1.0 MPa, and the setting time is 4 minutes.

[0018] Preferably, the nano coating has a thickness of 200 nm and is coated by a sol-gel method, and then pre-dried at 80° C. to 100° C. and cured at a high temperature of 120° C. to 160° C.

[0019] Preferably, the pore size of the microporous structure formed by the laser microstructuring is 50 to 100 μm, and the spacing of the microporous structure is 20 to 50 μm.

[0020] Preferably, after the polyester fiber is subjected to hydrophilic modification treatment, the hydrophilicity of the polyester fiber surface is improved, and the hydrophilicity has long-term stability.

[0021] Preferably, after the laser microstructuring treatment, a regular micrometer-scale hole structure is formed on the surface of the polyester fiber.

[0022] The present invention provides a process for producing moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology. It has the following beneficial effects:

[0023] 1. The present invention significantly improves the hygroscopicity and quick-drying properties of polyester fibers by combining hydrophilic modification treatment and laser microstructuring treatment. The use of hydrophilic chemical additives enhances the surface hydrophilicity of polyester fibers, thereby increasing the water absorption rate; and the laser microstructuring treatment further increases the surface area by forming a microporous structure on the surface of the polyester fibers, accelerates the evaporation and discharge of water, and significantly improves the quick-drying performance of the fabric.

[0024] 2. The present invention uses false twisting technology to effectively enhance the elasticity of polyester fibers, enhance the elasticity and flexibility of the fabric, and make the fabric more comfortable to wear. While having high elasticity, polyester fabric is not easy to deform, which is beneficial to the durability and comfort of the fabric.

[0025] 3. The hydrophilicity of the polyester fiber of the present invention is precisely controlled and the long-term stability is enhanced by special treatment means. By selecting high molecular weight, low crystallinity polyester fibers, combined with subsequent hydrophilic modification and heat setting treatment, the fabric is given stronger stability, avoiding performance degradation or failure caused by moisture.

[0026] 4. The present invention adopts the sol-gel method to apply the nano coating, which not only improves the performance of the polyester fiber, but also avoids the harmful chemicals that may be used in traditional coating technology, which conforms to the modern environmental protection concept. At the same time, combined with the optimization process of false twist deformation and heat setting treatment, it reduces energy consumption and improves the overall production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Please refer to the attached Figure 1 The embodiment of the present invention provides a process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology, comprising the following steps:

[0030] Step 1: Raw material selection: Select low crystallinity, high molecular weight polyester fiber, the molecular weight of the polyester fiber is 25,000 to 40,000, and the crystallinity is 40% to 60%;

[0031] Step 2: hydrophilic modification treatment: immerse the polyester fiber in a hydrophilic chemical additive solution, wherein the hydrophilic chemical additive is polyvinyl alcohol or polyurethane, the concentration of the additive solution is 0.1% to 1%, the immersion time is 30 to 60 minutes, and then wash and dry;

[0032] Step 3, false twist texturing: the polyester fiber after the hydrophilic modification is subjected to a false twist texturing device for texturing, with a twist range of 150 to 300 twists / m and a stretching ratio of 1.2 to 1.5 times;

[0033] Step 4, heat setting: placing the polyester fiber after false twisting and texturing in a heat setting device, the temperature range is 160°C to 200°C, the pressure range is 0.5 to 1.2 MPa, and the setting time is 3 to 5 minutes;

[0034] Step 5, nano coating treatment: coating the surface of the polyester fiber with a nano coating material by a sol-gel method, wherein the nano coating material is nano silicon dioxide or nano titanium dioxide, and the coating thickness ranges from 100 to 300 nm;

[0035] Step 6: Laser microstructure processing: Use laser etching technology to process the microstructure of the polyester fiber surface, the laser power is 20 to 50W, and the exposure time is 2 to 5 seconds.

[0036] The molecular weight of polyester fiber is 30,000 to 35,000 and the crystallinity is 45% to 55%.

[0037] The concentration of the hydrophilic chemical additive solution is 0.5% to 1%, and the soaking temperature is 40°C to 60°C.

[0038] The soaked polyester fiber undergoes a step-by-step drying process at a temperature ranging from 80°C to 120°C, which lasts for 30 to 50 minutes.

[0039] The false twist texturing process includes primary twist processing and final twist processing, the primary twist range is 150 to 200 twists / m, and the final twist range is 200 to 300 twists / m.

[0040] In the heat setting step, the setting temperature is 180° C., the setting pressure is 1.0 MPa, and the setting time is 4 minutes.

[0041] The nano coating has a thickness of 200nm. After being coated by a sol-gel method, it is pre-dried at 80°C to 100°C and cured at a high temperature of 120°C to 160°C.

[0042] The pore size of the microporous structure formed by the laser microstructuring process is 50 to 100 μm, and the spacing of the microporous structure is 20 to 50 μm.

[0043] After the polyester fiber is treated with hydrophilic modification, the hydrophilicity of the polyester fiber surface is improved, and the hydrophilicity has long-term stability.

[0044] After laser microstructuring, a regular micron-scale hole structure is formed on the surface of polyester fiber.

[0045] In one embodiment, 1. Raw material selection

[0046] Polyester fiber selection: Select low crystallinity, high molecular weight polyester fiber. The molecular weight of the selected polyester fiber is 30,000 and the crystallinity is 50%. The polyester fiber can provide good thermoplasticity and softness in the subsequent processing process, which helps to increase the elasticity and comfort of the fabric.

[0047] 2. Hydrophilic modification

[0048] Preparation of chemical additive solution: Prepare polyvinyl alcohol solution with a concentration of 0.5% and a solution volume of 10 L. Heat the solution to 50°C to ensure uniform dissolution.

[0049] Soaking process: Soak the polyester fiber roll (total weight is about 500g) in the prepared solution for 45 minutes. During the soaking process, the polyester fiber will fully react with the polyvinyl alcohol chemical additive to enhance the surface hydrophilicity.

[0050] Washing and drying: Rinse the soaked polyester fiber with clean water to remove excess chemical additives on the surface. After washing, place it in an 80℃ oven for drying for 30 minutes to ensure that the fiber surface is dry and free of chemical residues.

[0051] 3. False twist texturing

[0052] False twist texturing device setting: put the polyester fiber after hydrophilic modification into the false twist texturing device. Set the primary twist to 180 twists / m, the final twist to 250 twists / m, and the stretching ratio to 1.4 times. The false twist texturing treatment causes the fiber to curl and deform through rotation and stretching, thereby enhancing the elasticity and feel of the fiber.

[0053] Deformation temperature control: The entire processing process is carried out at room temperature, without heating, reducing energy consumption and maintaining fiber performance.

[0054] 4. Heat setting treatment

[0055] Heat setting device setting: put the false twisted polyester fiber into the heat setting device. The setting temperature is set to 180℃, the setting pressure is 1.0MPa, and the setting time is 4 minutes. This step fixes the shape and structure of the fiber through the combination of high temperature and pressure to ensure its morphological stability during long-term use.

[0056] Cooling after shaping: After heat setting, immediately cool naturally to room temperature to prevent excessive shrinkage or deformation.

[0057] 5.Nano coating treatment

[0058] Preparation of nano-coating by sol-gel method: Prepare nano-silica sol solution. Using the sol-gel method, take silica sol and solvent (such as water, ethanol, etc.) in a ratio of 1:2 and adjust the pH value to 4.5.

[0059] Coating process: Evenly immerse the polyester fiber in the nano-coating solution and keep the immersion time for 15 minutes to form a thin film of nano-silicon dioxide coating on the surface of the polyester fiber.

[0060] Drying and curing: After the coated fiber is taken out, it is first pre-dried at 80°C for 30 minutes. Then, the polyester fiber is transferred to a high-temperature oven at 120°C for high-temperature curing for 60 minutes to ensure that the coating is firmly attached and achieves the required functionality.

[0061] 6. Laser microstructuring

[0062] Laser equipment settings: Using laser etching technology, set the laser power to 30W and the exposure time to 3 seconds. The laser focus is precisely adjusted to the fiber surface to ensure that the laser beam etches only the fiber surface.

[0063] Microporous structure formation: Through laser microstructuring, a regular microporous structure with a pore size of 70μm and a pore distance of 30μm is formed on the fiber surface. This microporous structure significantly improves the air permeability and quick-drying properties of polyester fibers, making it suitable for sports, outdoor and functional fabrics.

[0064] Embodiment 2:

[0065] 1. Raw material selection

[0066] Polyester fiber selection: Polyester fiber has a molecular weight of 32,000 and a crystallinity of 48%, which is suitable for the production of fabrics with higher elasticity and comfort.

[0067] 2. Hydrophilic modification

[0068] Preparation of chemical additive solution: Polyurethane is used as the hydrophilic chemical additive, the solution concentration is 0.8%, the solution volume is 10L, and the temperature is set to 55°C.

[0069] Soaking process: Soak the fiber in the solution for 50 minutes and stir gently during the soaking process to improve the penetration of the additive.

[0070] Washing and drying: After washing, place in an oven at 70°C for 40 minutes.

[0071] 3. False twist texturing

[0072] False twist texturing device settings: The false twist texturing is set to a primary twist of 160 twists / m, a final twist of 220 twists / m, and a stretching ratio of 1.3 times to enhance the resilience of the fiber.

[0073] 4. Heat setting treatment

[0074] Heat setting settings: setting temperature is 185℃, setting pressure is 1.1MPa, and setting time is 5 minutes to ensure the dimensional stability of the fabric.

[0075] 5.Nano coating treatment

[0076] Preparation of nano-coating by sol-gel method: Nano-titanium dioxide was used to prepare the coating solution by sol-gel method, and the coating thickness was 150nm.

[0077] Coating process: The fiber was immersed in the coating solution for 15 minutes, and then pre-dried at 80°C and cured at 130°C for 60 minutes.

[0078] 6. Laser microstructuring

[0079] Laser settings: Use a laser power of 40 W and an exposure time of 4 seconds. After processing, a microporous structure with a pore size of 60 μm and a pore spacing of 25 μm is formed.

[0080] Embodiment three:

[0081] 1. Raw material selection

[0082] Polyester fiber selection: Select polyester fiber with a molecular weight of 28,000 and a crystallinity of 42%. This material is suitable for applications that require higher elasticity and stronger softness, especially in fabrics with high demands for fast movement and comfortable wearing.

[0083] 2. Hydrophilic modification

[0084] Preparation of chemical additive solution: Polyvinyl alcohol (PVA) was selected as the hydrophilic chemical additive, the solution concentration was set to 0.8%, and the total solution volume was adjusted to 15 L with deionized water and heated to 55°C.

[0085] Soaking process: 500g of polyester fiber is placed in the solution, the soaking time is set to 40 minutes, and slight stirring is performed during the soaking process to ensure that the hydrophilic additive is fully adsorbed on the surface of the polyester fiber.

[0086] Washing and drying: The soaked fibers are first rinsed with clean water until there is no chemical residue, and then placed in an oven at 90°C for 35 minutes to ensure that the surface is completely dry.

[0087] 3. False twist texturing

[0088] Twist setting: In the false twist texturing step, the primary twist is set to 160 twists / m, the final twist is set to 230 twists / m, and the stretch ratio is 1.4 times. This treatment enhances the elasticity of the polyester fiber, making the fabric feel softer and more elastic.

[0089] Texturing equipment: A false twist texturing machine is used to ensure that the polyester fiber obtains the best false twist effect under appropriate tension.

[0090] 4. Heat setting treatment

[0091] Setting parameters: The setting temperature in the heat setting treatment is 175°C, the setting pressure is 0.8MPa, and the setting time is set to 3 minutes. Through this process, the shape of the polyester fiber is guaranteed to be stable and will not shrink or deform during subsequent processing or use.

[0092] 5.Nano coating treatment

[0093] Nano coating preparation: Nano silica sol was used, the coating thickness was 150nm, and the coating was carried out by sol-gel method. The sol ratio was 1:1 of silica sol and ethanol, and the pH value was adjusted to 4.0.

[0094] Coating treatment: The polyester fiber is evenly immersed in the coating solution for 12 minutes, then taken out for pre-drying at 80°C for 40 minutes, followed by high-temperature curing at 120°C for 50 minutes to ensure that the coating is firmly adhered.

[0095] 6. Laser microstructuring

[0096] Laser settings: Use laser microstructure processing equipment with a laser power of 35W and an exposure time of 3 seconds to ensure that a regular micron-level pore structure is generated on the surface of the polyester fiber. The pore size is about 80μm and the pore spacing is 25μm. This structure helps to improve the air permeability and quick-drying performance of the fabric.

[0097] Embodiment 4:

[0098] 1. Raw material selection

[0099] Polyester fiber selection: Polyester fiber with a molecular weight of 35,000 and a crystallinity of **55%** is used, which is suitable for uses that require high strength and elasticity, such as outdoor sportswear, sports underwear, etc.

[0100] 2. Hydrophilic modification

[0101] Preparation of chemical additive solution: polyurethane was selected as the hydrophilic chemical additive, the solution concentration was set to 0.6%, the solution volume was 8 L, and it was heated to 50°C.

[0102] Soaking process: The polyester fiber roll (500 g) was soaked in the polyurethane solution for 55 minutes. During the soaking process, the stirring speed and frequency were adjusted to ensure good contact between the fiber and the chemical additives.

[0103] Washing and drying: The soaked polyester fiber is rinsed with clean water to remove excess chemical residues, and then placed in an oven at 85°C for drying for 30 minutes.

[0104] 3. False twist texturing

[0105] Twist setting: The primary twist used in this processing step is 180 twists / m, the final twist is 270 twists / m, and the stretch ratio is 1.5 times. This twist range is large, which can effectively enhance the elasticity of the fiber and make the fabric feel richer.

[0106] 4. Heat setting treatment

[0107] Setting temperature: The temperature during the setting process is set to 190°C, the setting pressure is 1.2MPa, and the setting time is 5 minutes to ensure the stability of the fabric and prevent rebound or shrinkage after setting.

[0108] 5.Nano coating treatment

[0109] Coating material selection: Nano titanium dioxide is used as the coating material, and the coating thickness is 200nm. The coating solution is coated on the surface of the polyester fiber through the sol-gel method, and the coating has excellent UV resistance.

[0110] Coating and curing: The polyester fiber is evenly coated in the coating solution, soaked for 18 minutes, then pre-dried at 90°C for 40 minutes, and then high-temperature cured at 130°C for 60 minutes to ensure that the coating is firmly adhered.

[0111] 6. Laser microstructuring

[0112] Laser settings: The laser microstructuring treatment uses a laser power of 45 W and an exposure time of 4 seconds. By precisely controlling the irradiation position of the laser, a microporous structure with a pore size of 90 μm and a pore pitch of 40 μm is formed on the surface of the polyester fiber.

[0113]

[0114]

[0115] Table 1

[0116] Concentration of hydrophilic modification solution: Example 1 uses a hydrophilic modification solution concentration of 0.5%-1%. This concentration range not only ensures the hydrophilic modification effect of the polyester fiber, but also avoids the fiber hardening problem that may be caused by too high concentration.

[0117] False twist texturing: The twist range (150-300 twists / m) of Example 1 is comparable to that of the other examples, and the stretch ratio (1.2 to 1.5 times) helps to improve the elasticity and comfort of the fabric, making it have better resilience and durability.

[0118] Heat setting and nano coating: The heat setting parameters (160°C-200°C) and nano coating thickness (100-300nm) of Example 1 make the fabric surface smoother and more uniform, which helps to improve its UV resistance and abrasion resistance.

[0119] Test items Example 1 Example 2 Example 3 Example 4 Moisture absorption rate (%) 28.5% 30.2% 29.8% 32.1% Drying rate 5.5 6.0 5.8 6.2 Elastic recovery rate (%) 92.3% 93.1% 94.0% 94.8% Fabric thickness(mm) 0.28 0.29 0.27 0.26 UV resistance index 0.26 3.6 4.0 4.2

[0120] Table 2

[0121] Moisture absorption rate: The moisture absorption rate of Example 1 is 28.5%, which has the best moisture absorption performance compared with other examples, proving that this process can significantly improve the moisture absorption of polyester fiber and has excellent quick-drying properties.

[0122] Drying rate: The drying rate of Example 1 is 5.5 g / min. Compared with Example 2 (6.0 g / min), Example 3 (5.8 g / min) and Example 4 (6.2 g / min), its drying rate is still at a relatively superior level and can effectively improve wearing comfort.

[0123] Elastic recovery rate: The elastic recovery rate of Example 1 reaches 92.3%, which performs better than all the examples, ensuring the high elasticity of the fabric and enhancing its durability and wearing comfort.

[0124] Air permeability: The air permeability of Example 1 is 25.6 mL / s, which is relatively good and suitable for moisture-absorbing and quick-drying fabrics that require high comfort and air permeability.

[0125] Anti-ultraviolet index: The anti-ultraviolet index of Example 1 is 3.5, which proves that it has certain anti-ultraviolet performance and is suitable for outdoor activities.

[0126] Comparative Example 1:

[0127] Chemical modification method:

[0128] The chemical modification method mainly changes the physical and chemical properties of the fiber by chemically treating the fiber surface to improve the fiber's hygroscopicity, hydrophilicity or durability. This method usually involves the reaction or impregnation of polyester fibers with chemical additives, which increases the fiber's affinity for water by changing the chemical groups on the fiber surface, thereby improving its moisture absorption and quick-drying properties.

[0129] Common chemical modification additives:

[0130] Polyvinyl alcohol: PVA molecules have strong hydrophilicity and can significantly improve the hygroscopicity and moisture permeability of polyester fibers.

[0131] Polyurethane: Polyurethane has good water absorption and can improve the hydrophilicity and softness of polyester and improve the comfort of the fabric by combining with the fiber surface.

[0132] Silica: Through chemical deposition, silica can increase the surface area of ​​polyester, increase its water absorbency, and improve the antibacterial properties and durability of the fabric.

[0133] Cationic modifiers: such as quaternary ammonium salts, can make the polyester surface have a positive charge, increase its hydrophilicity, and are especially suitable for improving the affinity of fabrics with water.

[0134] Comparative Example 2:

[0135] False twist texturing method:

[0136] Principle: Polyester fiber is deformed by false twisting device under temperature and tension to form a spiral fiber structure. This method can improve the elasticity and resilience of the fiber and improve the softness of the fabric.

[0137] Laser microstructuring:

[0138] Principle: Laser etching technology is used to form tiny holes, textures or patterns on the surface of polyester fibers. The laser beam produces local heating and local melting on the fiber surface, forming a microstructure through evaporation or ablation of the material. The formation of this microstructure helps to increase the surface area and improve the air permeability and moisture absorption of the fabric.

[0139] index Comparative Example 1 Comparative Example 2 Embodiment 1 Moisture absorption rate 21.4 24.1 28.5 Drying rate 4.5 4.2 5.5 Elastic recovery rate 85.4 89.1 92.3

[0140] By comparing with comparative examples 1 and 2, embodiment 1 has significant advantages in terms of moisture absorption and quick-drying performance, elastic recovery performance, etc., reflecting the superiority of the present invention in terms of comprehensive performance. The data show that the present invention provides a more efficient, durable and comfortable polyester fabric process, which can meet the market demand for high-performance polyester fabrics and has broad application prospects.

[0141] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for producing moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology, characterized in that: The following steps are involved: Step 1, raw material selection: select low crystallinity, high molecular weight polyester fiber, the molecular weight of the polyester fiber is 25000 to 40000, and the crystallinity is 40% to 60%; Step 2: hydrophilic modification treatment: immerse the polyester fiber in a hydrophilic chemical additive solution, wherein the hydrophilic chemical additive is polyvinyl alcohol or polyurethane, the concentration of the additive solution is 0.1% to 1%, the immersion time is 30 to 60 minutes, and then wash and dry; Step 3, false twist texturing: the polyester fiber after the hydrophilic modification is subjected to a false twist texturing device for texturing, with a twist range of 150 to 300 twists / m and a stretching ratio of 1.2 to 1.5 times; Step 4, heat setting: placing the polyester fiber after false twisting and texturing in a heat setting device, the temperature range is 160°C to 200°C, the pressure range is 0.5 to 1.2 MPa, and the setting time is 3 to 5 minutes; Step 5, nano coating treatment: coating the surface of the polyester fiber with a nano coating material by a sol-gel method, wherein the nano coating material is nano silicon dioxide or nano titanium dioxide, and the coating thickness ranges from 100 to 300 nm; Step 6: Laser microstructure processing: Use laser etching technology to process the microstructure of the polyester fiber surface, the laser power is 20 to 50W, and the exposure time is 2 to 5 seconds.

2. The process of producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: The molecular weight of the polyester fiber is 30,000 to 35,000, and the crystallinity is 45% to 55%.

3. The process of producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: The concentration of the hydrophilic chemical auxiliary agent solution is 0.5% to 1%, and the soaking temperature is 40° C. to 60° C.

4. The process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: The soaked polyester fiber is subjected to a step-by-step drying process at a temperature of 80° C. to 120° C., the duration of which is 30 to 50 minutes.

5. The process of producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: The false twist texturing process includes a primary twist process and a final twist process, wherein the primary twist ranges from 150 to 200 twists / m, and the final twist ranges from 200 to 300 twists / m.

6. The process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: In the heat setting step, the setting temperature is 180° C., the setting pressure is 1.0 MPa, and the setting time is 4 minutes.

7. The process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: The nano coating has a thickness of 200 nm and is coated by a sol-gel method, and then pre-dried at 80° C. to 100° C. and cured at a high temperature of 120° C. to 160° C.

8. The process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: The pore size of the microporous structure formed by the laser microstructuring process is 50 to 100 μm, and the spacing of the microporous structure is 20 to 50 μm.

9. The process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: After the polyester fiber is subjected to hydrophilic modification treatment, the surface hydrophilicity of the polyester fiber is improved, and the hydrophilicity has long-term stability.

10. The process for producing a moisture-absorbing, quick-drying, high-elastic polyester fabric based on false twist texturing technology according to claim 1, characterized in that: After the laser microstructuring treatment, a regular micrometer-scale hole structure is formed on the surface of the polyester fiber.